Meta-model of EPortfolio Usage in Different Environments - Balaban, Igor; Divjak, Blazenka; Mu, Enrique (International Journal of Emerging Technologies in Learning (iJET), 2011)
EPortfolio offers a new philosophy of teaching and learning, giving the learner an opportunity to express oneself, to show oneâ??s past work and experience to all the interested parties ranging from teachers to potential employers. However, an integral model for ePortfolio implementation in academic institutions that would take into account three different levels of stakeholders: 1. Individual (student and teacher); 2. Institution; and 3. Employer, currently does not exist. In this paper the role of ePortfolio in academic environment as well as the context in which ePortfolio operates is analyzed in detail. As a result of the comprehensive analysis that takes into account individual, academic institution and employer, a meta-model of ePortfolio usage in Lifelong Learning is proposed.